ACL injury prevention in European women’s football: exploring knowledge, attitudes and practices in a cross-sectional study - Evert Verhagen; Katrine Okholm Kryger; Gabriel Monthuley (BMJ Open Sport & Exercise Medicine)
Objective To assess the knowledge, attitudes and behaviours regarding anterior cruciate ligament (ACL) injury prevention among individuals involved in women’s football at all levels, including players and staff across Union of European Football Associations (UEFA) nations.Methods A cross-sectional, questionnaire-based survey was conducted to evaluate the knowledge, attitudes and behavioural adoption of ACL injury prevention strategies among players, coaches, medical staff and other stakeholders in European women’s football.Results A total of 2384 responses from 47 of the 55 UEFA national associations were analysed. While 95% of participants demonstrated awareness of ACL injuries, knowledge of specific exercise programmes to prevent such injuries was limited in coaches (62%) and players (32%), particularly at grassroots and recreational levels. Participants expressed positive attitudes towards integrating prevention programmes into regular routines with 97% expressing they would perform it if it significantly reduced ACL injuries; however, the actual implementation of these programmes remained low across all levels of play with 22% of players, 51% of coaches and 61% of medical staff reported having performed or facilitated an ACL prevention exercise programme.Conclusion Despite positive attitudes towards ACL injury prevention, the practical application of prevention programmes in women’s football is insufficient, especially below the national top-division level. This highlights the need for targeted educational initiatives to enhance knowledge and facilitate implementation among recreational players, coaches and medical staff.